Pie camp : the skills you need to make any pie you want - McDermott, Kate, 1953- (The Countryman Press, a division of W.W. Norton & Company, 2020)
The James Beard Award-nominated Pie Camp instructor presents a follow-up to Art of the Pie that shares expert insights into pie foundations, troubleshooting and mix-and-matching crusts with fillings, providing gluten-free options and one dozen master-level recipes.